Sacral nerve stimulation can alleviate symptoms of bowel dysfunction after colorectal resections. (2nd August 2017) - Mege, D.; Meurette, G.; Vitton, V.; Leroi, A.‐M.; Bridoux, V.; Zerbib, P.; Sielezneff, I.; ,
Abstract: Aim: Poor functional results, such as faecal incontinence (FI), low anterior resection syndrome (LARS) or high stool frequency, can occur after colorectal resections, including proctocolectomy with ileal pouch‐anal anastomosis (IPAA), rectal resection and left hemicolectomy. Management of such patients is problematic, and some case reports have demonstrated the effectiveness of sacral nerve stimulation (SNS) in these situations. Our aim was to analyse the effectiveness of SNS on poor functional results and on quality of life in patients after treatment with different types of colorectal resection. Method: At five university hospitals from 2006 to 2014, patients with poor functional results after rectal resection, IPAA or left hemicolectomy underwent a staged SNS implant procedure. Failure was defined by the absence or insufficient improvement (< 50%) of FI episodes. Results: SNS for bowel dysfunction was performed in 16 patients after rectal resection with coloanal anastomosis, left hemicolectomy with colorectal anastomosis or IPAA. Two (13%) cases of primary failure were observed after the percutaneous stimulation test. Median frequency of stool, FI episodes and urgency were significantly improved in 14 patients. Wexner and LARS scores were also significantly improved for 14 patients. When we compared results according to the type of colorectal surgery (IPAA, rectal resection or left hemicolectomy), median frequencies of stool and urgency, Wexner and LARS scores were still significantly improved. Overall success rate was 75% (12/16 patients) in intention‐to‐treat analysis and 86% (12/14 patients with permanent electrode) in per‐protocol analysis. Conclusion: SNS seems to improve bowel dysfunction following rectal resection, left hemicolectomy or IPAA.